Ten-year experience with the Swenson procedure in Nigerian children with Hirschsprung′s disease - Sowande Oludayo; Adejuyigbe Olusanya (African Journal of Paediatric Surgery, 2011)
Background: Hirschsprung′s disease (HD) is a common cause of intestinal obstruction in children. Definitive treatments consist of excision of the aganglionic segment and anastomosing the normal colon to the anal remnant. The outcome of this approach in Nigerian children is not known. The aim of this study was to analyze the short to mid-term outcome of children who have undergone the Swenson Procedure (SPT) as a treatment of HD over a period of 10 years. Patients and Methods: The clinical data of biopsy-proven cases of HD managed at the Obafemi Awolowo University Teaching Hospital, Ile-Ife, Nigeria, between 1998 and 2007 were reviewed. Results: There were 33 children 28 were males and five were females (M 5.6: F = 1). The median age at presentation was eight months (range three days to 11 years). Eighteen (54.5%) patients had primary pull-through without colostomy while 15 (45.5%) patients had a two-staged operation. The operation was carried out at a median age of 14 months with a range of seven weeks to 11 years, four months. Twenty-one (64%) of the patients were older than one year at the time of surgery. The level of aganglionosis was in the recto-sigmoid area in 30 (91%) patients. The commonest post-SPT complication was intestinal obstruction from adhesions. Bowel opening varied from once daily to eight times daily, median thrice daily. Conclusion: The Swenson′s Procedure is an effective procedure in the treatment of HD in children in Ile Ife, Nigeria.